Penggunaan Desain Pembelajaran Berbasis Inkuiri dalam Meningkatkan Pemahaman Konseptual Siswa - Maryam R. Aisy; Frandita Juwika; Gusmaneli Gusmaneli (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The purpose of this research is to analyze the use of inquiry-based learning design in improving students' conceptual understanding. This research uses the literature study method. The literature study method is conducted by collecting and reviewing various relevant literature, including scientific journals, books, articles, and research reports that discuss the topic of inquiry-based learning and its relation to students' conceptual understanding. The results of this study show that inquiry-based learning strategy is an approach that places students as the center of learning, encouraging them to think critically and discover knowledge independently, while the teacher acts as a facilitator in the process of formulating problems to draw conclusions. This method is effective for developing students' cognitive, affective and psychomotor abilities and adapts to their individual learning styles, although it can be a challenge for students who are used to conventional learning. Meanwhile, students' concept understanding includes the ability to master, apply, and explain a concept through various indicators, such as giving examples, distinguishing, and applying concepts in various situations.